ANALISIS PERAN GURU DALAM MENANAMKAN NILAI KARAKTER MELALUI PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN PADA SISWA SEKOLAH DASAR - Azimah, Siti; Munjiatun; Astuti Mulyani, Eva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of instilling character values in elementary school students amidst the challenges of globalization that affect the behavior of the younger generation. The purpose of this study is to describe the role of teachers in instilling character values through Civic and Pancasila Education (PPKn) learning. This study uses a qualitative approach with a phenomenological method. The research subjects consisted of fourth-grade PPKn teachers, the principal, and fourth-grade students at SD Negeri 188 Pekanbaru. Data collection techniques were carried out through in-depth interviews. Data analysis used the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the role of teachers in instilling character values includes the role as a role model, inspirator, motivator, dynamic facilitator, and evaluator. The most dominant role is as a role model through (1) habituating to pray before and after learning, (2) showing discipline by arriving on time, conducting learning according to schedule, and being brave enough to admit mistakes, (3) actively participating in group work, (4) using Indonesian in the learning process, implementing agreed-upon rules, and (5) demonstrating earnestness in fulfilling teaching responsibilities by conducting structured learning.